Multidimensional Experimental Characterization of Lumbar Spinal Deformity - Emma C. Coltoff; Alexander Hooke; Asghar Rezaei; Philip J. Brown (Annals of Biomedical Engineering, 2026)
Purpose Spinal deformities and motions of the spinal joints are rarely confined to a single anatomical plane. Yet diagnosis of such deformities and characterizations of their biomechanical behavior under load are often limited to two-dimensional methods of analysis. This study presented a testing methodology and visualization method to characterize the biomechanical responses of the intact and deformed lumbar spine under combined loading in multiple dimensions simultaneously. Methods Two L1–L5 lumbar spinal specimens underwent loading by five custom trajectories (rays, clockwise and counterclockwise petals and circles), each intended to perturb different responses of the spinal joints within the same range of motion. Results Multidimensional loading highlighted differing regions of spinal stiffness between intact and deformed specimens that do not fall along the sagittal and coronal planes. The rays trajectory crucially captured the non-linear, hysteretic behavior of planar loading and unloading patterns of the spine but also suggested a potentially misleading isotropy of spinal behavior relative to the craniocaudal axis. The petals and circles trajectories appropriately capture the anisotropy of spinal bending between the sagittal and coronal planes. The clockwise and counterclockwise versions of these trajectories emphasize how deformity impacts this anisotropy in both the neutral and elastic zones. Conclusion The insights from these trajectories highlight nuances of biomechanical behavior of the lumbar spine and disruptions due to deformity that would not be captured by pure moment loading alone. Introducing multidimensional characterization of biomechanical differences holds promise to supplement future clinical considerations for treatment of spinal deformity.